The Chronotope of Cultural-Historical Science of Activity - Meshcheryakov B.G. (Moscow State University of Psychology and Education, 2021)
This is the paper written by our late colleague and friend, Boris G. Meshcheryakov, “The Chronotope of Cultural-Historical Science of Activity”. We have decided to publish it as it is, without any editorial corrections or changes. This decision was informed not only by our wish to honor the memory of a talented scientist, but also by the fact that this paper is highly professional, smart and challenging. No alterations needed. Boris D. Elkonin